2000
DOI: 10.1093/carcin/21.11.1971
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 polymorphism and lung cancer risk in African-Americans

Abstract: Glutathione S:-transferase M1 (GSTM1) can detoxify many carcinogens, including polycyclic aromatic hydrocarbons such as those from cigarette smoke. Though a number of studies have been published about the association between GSTM1 polymorphism and lung cancer, this association has received limited attention in the African-American population. We conducted a case-control study to investigate the role of GSTM1 polymorphism in the development of lung cancer in African-Americans. Specimens of DNA from 117 lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 21 publications
0
48
0
1
Order By: Relevance
“…There is, indeed, increasing evidence showing that polymorphisms in specific genes can be associated with diseases, e.g. lung cancer (25) or cardiovascular disease (26). Thus, we investigated 20 healthy control patients for the presence (and incidence) of the Gly-to-Ser mutation.…”
Section: Resultsmentioning
confidence: 99%
“…There is, indeed, increasing evidence showing that polymorphisms in specific genes can be associated with diseases, e.g. lung cancer (25) or cardiovascular disease (26). Thus, we investigated 20 healthy control patients for the presence (and incidence) of the Gly-to-Ser mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Individual case control studies, as well as pooled and meta analyses have confirmed this hypothesis to some extent, so that for example the deletion of GSTM1 variant was found to be associated with various cancer types, both alone and in combination with other genetic polymorphisms. [7][8][9][10] Careful analysis of the literature reveals a much more murky picture for the GSTT1 gene than for GSTM1. Although one group reported GSTT1 to be a risk factor for lung cancer, 11 the majority of studies have found no association between GSTT1 deletion and cancer as shown by a meta and pooled analysis, 12 and in general there are more negative findings for this variant than for the GSTM1 deletion.…”
mentioning
confidence: 99%
“…Although many studies have shown that GSTM1 null genotype and variant CYP1A1 alleles are associated with an increased risk of lung squamous cell carcinoma (SCC) independent of the ethnic background, the results regarding lung AC risk are still contradictory. [3][4][5][6][7][8][9][10][11] A number of studies have also investigated the association of the genetic polymorphism of CYP2E1 with lung cancer, but the effects remain unclear. 6,[12][13][14][15][16][17][18][19][20][21][22] In the Chinese population, lung cancer is the leading cause of cancer deaths, and while SCC is still the predominant histological type, the rate for lung AC is increasing and AC is already the most common histological type in females.…”
mentioning
confidence: 99%